2013
DOI: 10.1016/j.virol.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of unfolded protein response, p53 and Akt in modulation of porcine reproductive and respiratory syndrome virus-mediated JNK activation

Abstract: Our previous study has shown that activation of JNK plays a critical role in Porcine reproductive and respiratory syndrome virus (PRRSV)-mediated apoptosis. In this follow-up study, we further investigated the mechanisms involved in modulation of PRRSV-mediated JNK activation and apoptosis. We found that unfolded protein response (UPR) was induced in response to PRRSV infection which in turn triggered JNK activation and apoptosis. We also found that p53 and Akt were activated at the early stage of infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 35 publications
7
32
2
Order By: Relevance
“…In this study, 3‐E‐5, 6‐D decreased the expression of XBP1s that induced by TiPs in fibroblasts. There were reports described that 3‐E‐5, 6‐D may inhibited phosphorylated Jun N‐terminal kinase (JNK) and LC3‐II, both of which acted downstream signaling of RANKL during osteoclast formation . Although we have not detected the effect of 3‐E‐5, 6‐D on JNK and LC3‐II in the present study, our data demonstrated that 3‐E‐5, 6‐D decreased TiPs‐induced RANKL expression by inhibiting XBP1s and treatment with 3‐E‐5, 6‐D was sufficient to decreased osteoclast formation by inhibiting the expression of RANKL.…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, 3‐E‐5, 6‐D decreased the expression of XBP1s that induced by TiPs in fibroblasts. There were reports described that 3‐E‐5, 6‐D may inhibited phosphorylated Jun N‐terminal kinase (JNK) and LC3‐II, both of which acted downstream signaling of RANKL during osteoclast formation . Although we have not detected the effect of 3‐E‐5, 6‐D on JNK and LC3‐II in the present study, our data demonstrated that 3‐E‐5, 6‐D decreased TiPs‐induced RANKL expression by inhibiting XBP1s and treatment with 3‐E‐5, 6‐D was sufficient to decreased osteoclast formation by inhibiting the expression of RANKL.…”
Section: Discussioncontrasting
confidence: 57%
“…It is known that PRRSV modulates apoptosis by multiple mechanisms . For example, PRRSV counteracts apoptosis of infected cells by activating the phosphatidylinositol‐3‐kinase‐dependent Akt pathway in the early stage of infection and promotes apoptosis by activating the c‐Jun N‐terminal kinase pathway in the late stage . In this study, altered expression levels were observed for several proteins involved in the positive or negative regulation of apoptosis, suggesting that these secreted proteins might contribute to modulation of apoptosis via cell‐to‐cell communications.…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows that activation of JNK signaling pathway is important in apoptosis induction of the host cells in responses to PRRSV infection (Yin et al, 2012). However, at the early stage of PRRSV infection, p53 and Akt are activated as negative regulator of ER-dependent JNK activation, which is in favor of the virus replication (Huo et al, 2013). In cell line MARC-2a stably expressing GP2a, the percentage of apoptotic cells is significantly decreased, suggesting that GP2a protein likely plays a role in apoptotic inhibition exerted by PRRSV (Pujhari et al, 2014).…”
Section: Modulation Of Apoptosismentioning
confidence: 99%
“…We also find that apoptosis occurs in both infected and non-infected cells, suggesting that apoptogenic cytokines, such as TNF␣, may be induced and involved in this process. Yin et al have shown that PRRSV infection activates JNK pathway in MARC-145 cells, and PRRSV-induced JNK activation is associated with ROS generation (Huo et al, 2013). Further studies have demonstrated that Bcl-2 family anti-apoptotic proteins Bcl-xl and Mcl-1 are down-regulated by PRRSV, which is dependent on JNK activation (Yin et al, 2012).…”
Section: Modulation Of Apoptosismentioning
confidence: 99%